1998
DOI: 10.1121/1.421200
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency backscattering enhancements by thick finite cylindrical shells in water at oblique incidence: Experiments, interpretation, and calculations

Abstract: Impulse response backscattering measurements are presented and interpreted for the scattering of obliquely incident plane waves by air-filled finite cylindrical shells immersed in water. The measurements were carried out to determine the conditions for significant enhancements of the backscattering by thick shells at large tilt angles. The shells investigated are made of stainless steel and are slender and have thickness to radius ratios of 7.6% and 16.3%. A broadband PVDF ͑polyvinylidene fluoride͒ sheet sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Of these waves, the a 0 wave has a phase velocity that depends significantly on frequency so that the tilt condition for the enhancement depends on frequency. This was confirmed by measuring the backscattering as a function of frequency over a wide range of scattering angles [6,10]. The a 0 wave studied was on the branch that is important above the coincidence frequency of the shell.…”
Section: Meridional Ray Enhancements For Tilted Cylindrical Shellsmentioning
confidence: 65%
See 4 more Smart Citations
“…Of these waves, the a 0 wave has a phase velocity that depends significantly on frequency so that the tilt condition for the enhancement depends on frequency. This was confirmed by measuring the backscattering as a function of frequency over a wide range of scattering angles [6,10]. The a 0 wave studied was on the branch that is important above the coincidence frequency of the shell.…”
Section: Meridional Ray Enhancements For Tilted Cylindrical Shellsmentioning
confidence: 65%
“…Away from the meridional ray coupling condition, qualitative measurements demonstrated that helical ray contributions can be significant [6,10,12,15]. A ray model for these enhancements was developed and confirmed with quantitative measurements of the backscattering of tone bursts [16] and the case of a water-filled shell was investigated [17].…”
Section: Helical Ray Backscattering Enhancements For Tilted Cylindricmentioning
confidence: 99%
See 3 more Smart Citations